Construction site, merry and bright : a Christmas lift-the-flap book - Rinker, Sherri Duskey; Ford, AG (San Francisco : Chronicle Books, 2021)
Told in rhyming text, the trucks decorate their construction site for Christmas.
Ages 2-4.
Keywords: Construction equipment -- Juvenile fiction; Christmas stories; Stories in rhyme; Lift-the-flap books -- Specimens; Board books; Stories in rhyme; Construction equipment -- Fiction; Christmas -- Fiction; Lift-the-flap books; Toy and movable books; Board books; Stories in rhyme; Lift-the-flap books